DIMENSI PENTING DISSENTING OPINION HAKIM DALAM MENYELAMATKAN KONSTITUSI DAN DEMOKRASI - Abustan Abustan (Jurnal Pengabdian kepada Masyarakat (J-PMas), 2024)
This study aims to determine the essence and important dimensions of the freedom or independence of judges in responding to / providing legal arguments regarding the dynamics of the Constitutional Court trial. This research method is an empirical study that uses a sociological legal approach. Meanwhile, the data collection technique is through observation and documents related to the trial at the Constitutional Court. The focus of the research is on the main discussion of dissenting opinions. The results of the discussion show new indications of the independence of the judge's attitude and views in adjudicating a dispute by showing different perceptions through dissenting opinions. It can be concluded that the judge's attitude/view in the context of this dispute is an "important dimension" in law enforcement in order to save the constitution and democracy, as well as provide legal enlightenment to the public. Therefore, dissenting opinion has an important meaning in the Constitutional Court's decision on the 2024 Presidential Election (decision number 1/PHPU.PRES-XXII/2024) and (decision number 2/PHPU.PRES-XXII/2024) which adjudicates constitutional cases at the first and final levels.